Ordre, durée et fréquence : la narratologie genettienne à la rescousse des récits brefs ? - Nicolas Garnier (Perspectives Médiévales)
The notion of « short narrative » is a real problem for medievalists, because it is at the crossroads of two issues: defining what narrative brevity is, and knowing if there is a « brief genre » for medieval literature. Gérard Genette’s works, mainly those related to narratology in Narrative Discourse, could then provide help. Notions of order, duration and frequencies developed by Gérard Genette to characterize stories could help us perceive the narrative unity of these omnifarious medieval texts. We studied six texts from the anthological manuscript 837 of the BnF: the Dit du Barisel, the Châtelaine de Vergy, Narcisse, the Enfant remis au soleil, the Vie de Sainte Élisabeth and the Vair Palefroi. Overall, there was some homogeneity: analepses and prolepses are somewhat undeveloped, there are few pauses, and beginnings are often iterative summaries. Nevertheless, some marked differences seem to show up there is no genre common to these texts. What is more, the tools developed by Genette, more devoted to concerns of temporality, seem too fragile to bring together these narratives: it is indeed difficult to determine whether a short text is necessarily a rapid text. Finally, Genette’s narratology exhibits more an aesthetics of brevity than a brief form or a brief genre.